2008
DOI: 10.1116/1.2943641
|View full text |Cite
|
Sign up to set email alerts
|

Survey on measurement of tangential momentum accommodation coefficient

Abstract: The value of tangential momentum accommodation coefficient (TMAC) is required while prescribing the boundary condition for flow of gases in the slip and transition flow regimes. The precise determination of its value is important for several other applications as well. This article reviews the experimental techniques employed by researchers over the decades to measure this coefficient and the values reported in the literature, with relevance to calculation of the slip velocity. The review shows that the value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(105 citation statements)
references
References 49 publications
3
102
0
Order By: Relevance
“…However, the flow in a tube is a two-dimensional problem, which is much simpler than that in a rectangular channel or a bundle of tubes where the problem could be a three-dimensional problem. It is also worth noting that the reported TMACs are still few (Agrawal and Prabhu 2008;Verma et al 2009) compared to EAC (Saxena and Joshi 1988), which is known to have a certain amount of variation among data in many cases. Therefore, the measurement of TMAC itself is important and valuable.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the flow in a tube is a two-dimensional problem, which is much simpler than that in a rectangular channel or a bundle of tubes where the problem could be a three-dimensional problem. It is also worth noting that the reported TMACs are still few (Agrawal and Prabhu 2008;Verma et al 2009) compared to EAC (Saxena and Joshi 1988), which is known to have a certain amount of variation among data in many cases. Therefore, the measurement of TMAC itself is important and valuable.…”
Section: Introductionmentioning
confidence: 95%
“…TMAC is known to vary depending on gas species, surface materials, surface temperature, surface conditions such as roughness and contaminant. TMAC has been measured by various approaches in a variety of gas-surface combinations and conditions (Agrawal and Prabhu 2008). Recently, TMAC was measured by the slip flow through microchannels fabricated by the semiconductor processing technique on silicon and related materials, which is often used for microdevices (Arkilic et al 2001;Maurer et al 2003;Colin et al 2004;Ewart et al 2006;Jang and Werely 2006;Ewart et al 2007a, b;Pitakarnnop et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…We consider both of these coefficients unity in studying diatomic nitrogen gas flow. Meanwhile, Agrawal and Prabhu (2008) have shown that the value of tangential momentum accommodation coefficient would be 0.926 for monatomic gas studies. Alexeenko et al (2002) showed that the dependency of nozzle flow solution to the accommodation coefficient is quite weak if this coefficient increases from 0.8 to 1.…”
Section: The Navier-stokes Solutionmentioning
confidence: 98%
“…The gas flow model can be used to find the TMAC of a gas on the surface of a microchannel by fitting mass flow measurements with the flow model (Agrawal and Prabhu 2008), which is now referred to as the microchannel flow method. The TMAC is an important parameter that is required to prescribe the boundary conditions in the gaseous slip or transition flow regimes, and it depends on wall material, gas flowing through the microchannels, and wall roughness.…”
Section: Introductionmentioning
confidence: 99%